THE EFFECTS OF NICOTINE EXPOSURE PER INHALATION TO THE CHANGE OF MOTILITY AND MORPHOLOGY OF THE RAT’S SPERM - Nugroho, Puruhito Eko; Rizaldi, Fikri; Soesanto, Wahjoe Djati (Indonesian Journal of Urology, 2019)
Objective: Smoking are known to have detrimental effect on sperm. The effects are suspiciously come from nicotine as its main pharmacologic component. This study is carried out to analyze the effect of nicotine exposure per inhalation to the difference of motile sperm percentage and normal morphology sperm percentage of male wistar rats. Material & Methods: Thirty male rats were used for this research. They were randomly divided into 5 groups and treated with nicotine inhalation 0.5 mg/kgBW,  1 mg/kgBW, 2 mg/kgBW and 4 mg/kgBW for 30 days while the control rats were not given any treatment. At the end of experiment, sperm analysis was carried out to measure the percentage of motile sperm and percentage of sperm with normal morphology. Results: Percentage of motile sperm significantly decreased (p<0.05) in all treatment groups compared to control group. Comparison between treatment groups revealed that the percentage of motile sperm significantly decreased in 0.5 mg/kgBW vs 2 mg/kgBW, 0.5 mg/kgBW vs 4 mg/kgBW, and 1 mg/kgBW vs 4 mg/kgBW. Percentage of normal morphology sperm decreased significantly (p<0.05) in 1 mg/kgBW, 2 mg/kgBW, and 4 mg/kgBW compared to control groups. Comparison between treatment groups revealed that there were no significant decreased between each treatment groups. Conclusion: This research conclude that nicotine exposure per inhalation can deteriorate the percentage of motile sperm and the percentage of normal morphology sperm of male wistar rats.